Second malignancy after radiotherapy for seminoma - Fuschshuber, Pascal R. (Radiology and oncology (Ljubljana), 1999)
A patient who developed a malignant peripheral nerve sheath tumor in the fieldof radiation 19 years after radiotherapy for stage I seminoma is presented. Data from recent population-based studies evaluating the risk of second malignancies in this group of patients is discussed. This case report illustrates the need for judicious evaluation of adjuvant radiotherapy in early stage seminoma patients.
Keywords: Adverse effects; Middle age; Neoplasms, second primary; Nerve sheath tumors; Radiotherapy; Seminoma; Testicular neoplasms